Questions of Truth vs. Questions of Trust: Nuancing the Influences of Religiosity, Political Conservatism, and Christian Nationalism on Attitudes Towards Science - Christopher P. Scheitle; Katie E. Corcoran; Bernard D. DiGregorio (Religions, 2025)
Religiosity and political conservatism are often hypothesized to be negatively associated with attitudes towards science. Yet, past research has often failed to distinguish between trust in science versus the acceptance of science as a source of truth. Using data generated from a probability survey of U.S. adults, we identify four latent factors within a battery of items asking about individuals’ views on science. Two of these represent science’s power as a source of truth, while the other two represent trust in science and scientists. A structural equation model finds that, all else being equal, measures of religiosity tend to be negatively associated with an individual’s view of science as a source of truth and unrelated to their trust in science. Adherence to Christian nationalism is negatively associated with an individual’s trust in science, while political conservatism and Republican identification is negatively associated with both trust in science and seeing science as a source of truth.